Polysaccharides as cell carriers for tissue engineering: the use of cellulose in vascular wall reconstruction - Bačáková, Lucie; Novotná, Kamila; Pařízek, Martin (Physiological research, 2014)
Polysaccharides are long carbohydrate molecules of monosaccharide units joined together by glycosidic bonds. These biological polymers have emerged as promising materials for tissue engineering due to their biocompatibility, mostly good availability and tailorable properties. This complex group of biomolecules can be classified using several criteria, such as chemical composition (homo- and heteropolysaccharides), structure (linear and branched), function in the organism (structural, storage and secreted polysaccharides), or source (animals, plants, microorganisms). Polysaccharides most widely used in tissue engineering include starch, cellulose, chitosan, pectins, alginate, agar, dextran, pullulan, gellan, xanthan and glycosaminoglycans. Polysaccharides have been applied for engineering and regeneration of practically all tissues, though mostly at the experimental level. Polysaccharides have been tested for engineering of blood vessels, myocardium, heart valves, bone, articular and tracheal cartilage, intervertebral discs, menisci, skin, liver, skeletal muscle, neural tissue, urinary bladder, and also for encapsulation and delivery of pancreatic islets and ovarian follicles. For these purposes, polysaccharides have been applied in various forms, such as injectable hydrogels or porous and fibrous scaffolds, and often in combination with other natural or synthetic polymers or inorganic nanoparticles. The immune response evoked by polysaccharides is usually mild, and can be reduced by purifying the material or by choosing appropriate crosslinking agents.
Keywords: cévy; Cellulose; biokompatibilní materiály; tkáňové inženýrství; Endothelial Cells; Biocompatible Materials; Cell Culture Techniques; Blood Vessels; tkáňové podpůrné struktury; Prosthesis Design; Blood Vessel Prosthesis; endoteliální buňky; Tissue Scaffolds; lidé; buněčné kultury; Guided Tissue Regeneration; celulosa; řízená tkáňová regenerace; cévní protézy; protézy - design; Animals; kultivované buňky; Humans; zvířata; Tissue Engineering; Cells, Cultured